Peran Pendidikan Anak Perempuan Dalam Membentuk Masyarakat Madani - Rosyida Nurul Anwar (Jurnal CARE (Children Advisory Research and Education), 2019)
The Islamic concept of child education is systematic, namely a concept that contains several educational components that are interconnected. The aim of girls' education is to develop knowledge and understanding of those involved in educating and developing children such as parents and teachers. In developing the potential of children from birth, quality formation begins with optimal readiness in various fields. Girls are educated to put basic human values as creatures of Allah SWT that is unique, unique, have potential, personality and interest in talent so that a high-civilized society can be realized optimally. The process of developing knowledge and skills by girls by planting the values of democracy, morality, faith, justice, tenderness, tolerance, egalitarianism, upholding the rights and obligations of women in society to build and empower people and qualified people who have competitive, creative abilities , innovative and accepting change so that education can bring prosperity to human life so that education received by girls will benefit greatly in the form of knowledge, strength, self-esteem, and unity.